Recent Progress Of Sol-gel Coating Of Pure Magnesium In Biomedical Applications. A Review - A.N. Aufa; Mohamad Zaki Hassan; Zarini Ismail (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2024)
Indexed by SCOPUS